Overcoming barriers to intranasal corticosteroid use in patients with uncontrolled allergic rhinitis - Bridgeman MB (Dove Medical Press, 2017)
Mary Barna Bridgeman1,2 1Department of Pharmacy Practice and Administration, Ernest Mario School of Pharmacy, Rutgers, The State University of New Jersey, Piscataway, NJ, USA; 2Department of Pharmacy, Robert Wood Johnson University Hospital, New Brunswick, NJ, USA Abstract: Patients suffering from allergic rhinitis often attempt to self-manage their symptoms and may seek advice from pharmacists about nonprescription product choices. Several drug classes, both prescription and over-the-counter (OTC), are available, including intranasal corticosteroids (INCSs); oral, intranasal, and ocular antihistamines; leukotriene antagonists; and topical and systemic decongestants, as well as immunotherapies. Selection of the optimal treatment approach depends on the temporal pattern, frequency, and severity of symptoms as well as the patient’s age. Nasal congestion is typically the most bothersome symptom, although rhinorrhea, postnasal drip, and ocular symptoms are also problematic. Together, these symptoms may adversely impact the quality of life, work productivity, sleep quality, and the ability to perform daily activities, particularly when uncontrolled. Practice guidelines recognize that INCSs are the most effective medications for controlling allergic rhinitis symptoms, including nasal congestion. Available INCS products have comparable safety and efficacy profiles, but they differ in formulation characteristics and sensory attributes. Several barriers can impede the use of INCSs, including concerns about safety, misperceptions regarding the loss of response from frequent use, and undesirable sensations associated with intranasal administration. Given the increasing number of INCSs available OTC, pharmacists can help allay these concerns by discussing treatment expectations, recommending INCS products with favorable formulation characteristics, and reviewing proper use and technique for the administration of the selected product. These steps can help to foster a collaborative relationship between the patient and the pharmacist in the treatment of allergic rhinitis. Keywords: allergy, nasal sprays, over-the-counter medications, patient counseling, pharmacy practice